PENGARUH PASTA GIGI YANG MENGANDUNG ENZIM TEHADAP PENURUNAN KADAR VOLATILE SULFUR COMPOUND : EFFECT OF ENZYME TOOTH PASTE IN DECREASING VOLATILE SULFUR COMPOUND LEVEL - Zulfan Muhammad Alibasyah; Irene Sukardi; Dewi Nurul Mustaqimah (Dentika: Dental Journal, 2011)
Halitosis or breath malodor may have negative efffect in communication. Halitosis is caused by chemical sulfur known as volatile sulfur compound (VSC) as a result of sulfur containing of amino acid degradation by anaerobic bacteria. Halitosis can be prevented by toothbrushing with tooth paste. The aim of this study was to analyze the effect of teeth and tongue brushing with dentrifice containing of amiloglucooxidase and glucooxidase enzyme. This experimental clinic study was conducted in the Clinic of Periodontology, Faculty of Dentistry, University of Indonesia. Subjects consisted of 77 students aged 17-30 years old, divided into 2 groups, 39 subjects conducted to brush their teeth and tongue with amiloglucooxidase and glucooxidase enzyme and 38 subjects conducted to brush their teeth and tongue with non enzyme tooth paste. The measurement of VSC level used cromatography gas, conducted after 30 minutes after teeth and tongue brushing. The result showed that there was no statical different in reducing VSC components in both groups (p>0,05). In conclusion, teeth and tongue brushing with dentrifice containing amiloglucooxidase and glucooxidase enzyme were not different to decrease the VSC level compared with non enzyme paste.